Arabic Language and Linguistics - Reem Bassiouney, E. Graham Katz (Georgetown University Press, 2012)
The Georgetown University Round Table on Languages and Linguistics (GURT) has been held since 1949, placing it among the most long-standing language and linguistics conferences in the United States. GURT began as a small gathering for researchers in language studies to share their current work and has gradually grown to become an internationally known forum for linguistic and language research, with an annual thematic focus. The theme of the 2010 Round Table was Arabic Language and Linguistics. At Georgetown and around the world, students are flocking to courses on Modern Standard Arabic and on Arabic linguistics. Arabic, one of the official languages of the United Nations, is spoken by more than half a billion people around the world and is of increasing importance in political and economic spheres. In addition the study of the Arabic language has a long and rich history: The earliest grammatical accounts date from the eighth century, and they include full syntactic, morphological, and phonological analyses of the vernaculars and of Classical Arabic. GURT 2010 was cohosted by the Department of Linguistics and by the Department of Arabic Language and Islamic Studies and was held March 12–14, with scholars of Arabic from around the world presenting research on various aspects of Arabic language study, from grammatical analysis to language pedagogy, and from sociolinguistic investigation to computational analysis. The invited speakers, whose work spanned this spectrum, were Mushira Eid, University of Utah; Ali Farghaly, formerly of Monterey Institute of International Studies and Cairo University, now at DataFlux Corporation; Catherine Miller, French Council of Research and Centre Jacques Berque; Karin Ryding, Georgetown University; and Yasir Suleiman, University of Cambridge. GURT 2010 drew more than 200 attendees from around the world, including many from Europe, Asia, North Africa, and the Middle East, making it the largest assemblage of Arabic language scholars in North America to date. Nearly eighty papers were presented in the main sessions, and another two dozen were presented in panel sessions. This volume includes a selection of the papers presented that represents the range and quality of research on the Arabic language in the twentyfirst century.